Trophic Status of the Koto Tibun Reservoir, Kampar District, Riau Province Based on Trophic State Index - Sitorus, Rike Yance; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Koto Tibun reservoir received organic and anorganic materials from the Tibun River. The impact of continous materials input caused enrichment of nutrient in the waters. This research aims to understand the trophic status of the Koto Tibun Reservoir based on trophic state index and it was conducted in February-March 2018. There were three stations namely, station 1( riverine zone), station 2 (transition zone) and station 3 (lacustrine zone). Samples were taken once/week for a 3 week period. Water quality parameters measured were total phosphorus, chlorophyll-a, transparency, temperature, pH, dissolved oxygen and nitrate. Result shown that total phosphorus was 144.94-192.48 µg/L, chlorophyll-a 3.10-3.98 µg/L, transparency 0.75-0.79 m, temperature 25.3-25.6 oC, pH 5, dissolved oxygen 4.78-5.62 mg/L and nitrate 0.186-0.193 mg/L. The TSI value (60.3-62.35) indicate that the Koto Tibun reservoir can be categorized as eutrophic. Keyword : Koto Tibun Dam, Water Quality, Trophic Status, Eutrophic